Common Functional Ability Score for Young People With Juvenile Idiopathic Arthritis. Issue 7 (4th June 2021) - Shoop‐Worrall, Stephanie J. W.; Oude Voshaar, Martijn A. H.; McDonagh, Janet E.; Van de Laar, Mart A. F. J.; Wulffraat, Nico; Thomson, Wendy; Hyrich, Kimme L.; Verstappen, Suzanne M. M.
Abstract : Objective: As young people enter adulthood, the interchangeable use of child and adult outcome measures may inaccurately capture changes over time. This study aimed to use item response theory (IRT) to model a continuous score for functional ability that can be used no matter which questionnaire is completed. Methods: Adolescents (ages 11–17 years) in the UK Childhood Arthritis Prospective Study (CAPS) self‐completed an adolescent Childhood Health Assessment Questionnaire (CHAQ) and a Health Assessment Questionnaire (HAQ). Their parents answered the proxy‐completed CHAQ. Those children with at least 2 simultaneously completed questionnaires at initial presentation or 1 year were included. Psychometric properties of item responses within each questionnaire were tested using Mokken analyses to assess the applicability of IRT modeling. A previously developed IRT model from the Pharmachild‐NL registry from The Netherlands was validated in CAPS participants. Agreement and correlations between IRT‐scaled functional ability scores were tested using intraclass correlations and Wilcoxon's signed rank tests. Results: In 303 adolescents, the median age at diagnosis was 13 years, and 61% were female. CHAQ scores consistently exceeded HAQ scores. Mokken analyses demonstrated high scalability, monotonicity, and the fact that each questionnaire yielded reliable scores. There was little difference in item response characteristics between adolescents enrolled in CAPS and Pharmachild‐NL (maximum item residual 0.08). Significant differences were no longer evident between IRT‐scaled HAQ and CHAQ scores. Conclusion: IRT modeling allows the direct comparison of function scores regardless of different questionnaires being completed by different people over time. IRT modeling facilitates the ongoing assessment of function as adolescents transfer from pediatric clinics to adult services.